Brief strategic family therapy - Szapocznik, José; Hervis, Olga (American Psychological Association, 2020)
"Brief Strategic Family Therapy (BSFT) is a strengths based model for diagnosing and changing repetitive patterns of behavior that cause friction in families. This clinical guide to BSFT shows how practitioners can transform family interactions from conflictive to collaborative, from habitual to proactive, so the love trapped behind anger can flourish. When, for example, a teen is acting out, using drugs, or not attending school, the adults in the family need to assume leadership, and all members of the family must adapt their patterns of talking and behaving with one another for positive changes to take place. BSFT therapists aid in this process by analyzing how the family operates as a whole and the role that each member plays in the family organism. Readers of this book will learn how to engage reluctant families or family members, and structure 12 to 16 week cognitive and affective interventions that will effect powerful behavior change. Detailed clinical examples show practitioners how to navigate family complexities, and work through the challenging decision points they present"--